Construction Research Congress 2014 2014
DOI: 10.1061/9780784413517.183
|View full text |Cite
|
Sign up to set email alerts
|

Developing a BIM-enabled Bilingual Safety Training Module for the Construction Industry

Abstract: This research documents and assesses the development of a construction safety training module featuring BIM-enabled 3D visualization narrated in both English and Spanish to test if such information can enhance safety training for construction management students and construction workers. A pilot (English version) of the module was administered to construction management students and their responses were generally positive. Spanish and English versions of the modules were then administered to professional mason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…As BIM has become the gold standard of the AEC industry, it is of significant importance that CM programs train future construction professionals in the capabilities and advantages of BIM technology [1,31], as lack of adequate training has been one of the challenges to move the industry into the BIM era [9,10]. Although a number of recent studies have suggested that integrating BIM into existing CM courses is the most practical approach, comprehensive frameworks have not been found that are able to provide a systematic coverage of BIM in a CM curriculum, and many CM programs are still struggling with its implementation and its alignment with existing CM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As BIM has become the gold standard of the AEC industry, it is of significant importance that CM programs train future construction professionals in the capabilities and advantages of BIM technology [1,31], as lack of adequate training has been one of the challenges to move the industry into the BIM era [9,10]. Although a number of recent studies have suggested that integrating BIM into existing CM courses is the most practical approach, comprehensive frameworks have not been found that are able to provide a systematic coverage of BIM in a CM curriculum, and many CM programs are still struggling with its implementation and its alignment with existing CM.…”
Section: Discussionmentioning
confidence: 99%
“…Since construction methods are practical topics, the traditional approach requires extensive field experiences from the instructor, and students often learn from the instructor's past experiences. This approach usually focuses on specific projects that the instructor has worked on and thus does not enhance student comprehension of how to apply the methods in other projects [31,32]. Using BIM models allows to demonstrate different architectural and structural components of the building and helps students visually see how they are connected to form a system, and further understand what methods are needed to complete the system [18].…”
Section: Sophomore Yearmentioning
confidence: 99%
“…elimination and substitution) are generally considered more effective, reliable and cost-efficient than the lower-level controls (CDC, 2018). Furthermore, when addressing safety issues using BIM, most studies have also only targeted a specific Research: (Kiviniemi et al, 2011;Azhar et al, 2012;Melzner et al, 2013;Sulankivi et al, 2013;Zhang et al, 2013;Collins et al, 2014;Kim et al, 2015;Kim et al, 2016) Research: (Azhar et al, 2012;Lee, Cho, Ham, Lee, Lee, Yun and Yang, 2012a;Chen et al, 2013;Clevenger et al, 2014;Shen and Marks, 2015) type of site hazard (e.g. falls).…”
Section: Introductionmentioning
confidence: 99%
“…One feature is its ability to help reduce waste during the design phase [27]. Clevenger et al [1] worked on 3D visualization describing a tool that is intended to enhance safety by reducing the impact of language differences on the jobsite. A safer design can be considered a sustainable design since it reduces the financial impact of injuries incidents on projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Increased focus on preventing injuries and fatalities and improvements in safety have occurred in recent years, however, the construction industry is still one of the three most dangerous work industries [1]. In the United States (US), there were 985 fatal injury cases in the construction industry during 2015 in comparison with 4836 cases for all other industries which makes the construction industry responsible for approximately 20% of all of fatal injury incidents [2].…”
Section: Introductionmentioning
confidence: 99%